Organic Glutinous Rice Seed Development: Dao Laum Deuan Organic Rice Seed Community Enterprise, Sakon Nakhon Province - Sattaka, Patcha (Area Based Development Research Journal, 2020)
Dao Laum Deuan Organic Rice Seed Community Enterprise was set up in 2017 with an aim to produce glutinous rice seeds for community use; however, the seeds had not obtained a certification of rice seed standard. Under the policy to promote organic rice production, the farmers want to develop the potential of glutinous rice seed production to meet the certified organic rice standards and seed standards. Thus, the objective of this research is to improve the organic glutinous rice seeds production for certification. The project employs participatory action research with 43 members of the Dao Laum Deuan Organic Rice Seed Community Enterprise. The research is divided into 3 phases, including 1) the preparation phase to prompt and survey the community for general information, 2) the research phase with community for problem identification and diagnosis, and planning for production development, and 3) the monitoring and evaluation especially the action for organic rice standard and rice seed standard. The practical guidelines to develop the farmers’ potential in organic glutinous rice seed production are knowledge transferring and sharing, building a group management system, rice seed production planning, controlling and monitoring the rice seed processes, and networking for the group. By the 2nd year of conversion period (T2), the production meets organic standard, and to date fourteen members have certified their rice seed standard. In conclusion, the glutinous rice production increased from 335 kilogram per rai to 382 kilogram per rai.